Obvladovanje tveganj v pomurski regiji: prispevek k uspešnosti poslovanja ter rasti vrednosti podjetij - Jagrič, Vita (Anali PAZU HD, 2026)
Keynes saw the uncertainty of the economy as the building block of uncertainty. The distinction between risk and uncertainty is evident in reality, a century later, and remains interesting from a theoretical perspective. Currently, the level of uncertainty in the economic environment is at extremely high levels, and the complexity of risks and their interconnectedness are increasing. In the paper, we found that part of large and medium-sized enterprises in the non-financial sector in the Pomurje region comprehensively manage risks, which strengthens the competitiveness of the company and contributes to the stable growth and development. The identified characteristics of enterprises in Pomurje are mostly comparable to the perceived characteristics of the all-Slovenian sample. The results are encouraging for growth and development in the region.
Keywords: celovito obvladovanje tveganj; Ekonomija; enterprise risk management; financial stability; growth of the company's value; rast vrednosti podjetja; risk and uncertainty; stabilnost finančnih rezultatov; subjective probability; subjektivna verjetnost; Tveganje; tveganje in negotovost